The Challenges of Projecting the Public Health Impacts of Marijuana Legalization in Canada; Comment on "Legalizing and Regulating Marijuana in Canada: Review of Potential Economic, Social, and Health Impacts" - Stephanie Lake; Thomas Kerr (Kerman University of Medical Sciences, 2017)
A recent editorial in this journal provides a summary of key economic, social, and public health considerations of the forthcoming legislation to legalize, regulate, and restrict access to marijuana in Canada. As our government plans to implement an evidence-based public health framework for marijuana legalization, we reflect and expand on recent discussions of the public health implications of marijuana legalization, and offer additional points of consideration. We select two commonly cited public concerns of marijuana legalization - adolescent usage and impaired driving - and discuss how the underdeveloped and equivocal body of scientific literature surrounding these issues limits the ability to predict the effects of legalization. Finally, we discuss the potential for some potential public health benefits of marijuana legalization - specifically the potential for marijuana to be used as a substitute to opioids and other risky substance use - that have to date not received adequate attention.